Design Thinking to Build a "Literacy Park" Inspired by the Hadith of the Prophet Muhammad - Dena Agustina; Wawan Hernawan (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in education. This research method is qualitative through literature study and field studies with a design thinking approach to build Litersi Park. The discussion of this research includes education today, the inspiration for the example of the Prophet. in providing benefits for others, and innovation to build literacy gardens. This research concludes that the hadith of the Prophet SAW. has inspirational messages in fostering a sense of empathy by providing benefits to others, in order to create harmony